PENDAMPINGAN MEMBIMBING ANAK YANG KESULITAN MEMBACA PADA ANAK SD KELAS II SDN PANGLEGUR 2 - Nafira; Salsabila, Ainan Rofika; Muzeyyenah (CV. Jendela Gagasan, 2024)
Reading is a fundamental skill in primary education. However, several second-grade students at SDN Panglegur 2 were found to struggle with reading, including letter recognition, syllable blending, and basic text comprehension. This community service project aimed to provide structured reading assistance using phonics-based, multisensory, and educational game methods. The program was conducted over six sessions, employing diagnostic reading tests, repeated reading exercises in individual and small group formats, and post-program evaluations. The participants were second-grade students with reading difficulties, supported by active involvement of teachers and parents. The results showed significant improvements in students' reading skills and self-confidence. The program also promoted a literacy culture and can serve as a replicable model for similar elementary school contexts..